Citizenship, disability rights and the changing relationship between formal and informal caregivers: it takes three to tango. Issue 2 (7th February 2020) - Dermaut, Vanessa; Schiettecat, Tineke; Vandevelde, Stijn; Roets, Griet
Abstract: Citizenship and rights conventionally refer to the ways in which the relationship between the individual and the state is constructed. These concepts concern the vital political and democratic values of freedom, equality and solidarity. As realising the citizenship and rights of disabled people has become an explicit aim of many western democratic governments, we explore in this article how these notions are encompassed in the formal rhetoric of social policy-makers. However, social policy rhetoric is potentially paradoxical when a critical consideration is made about how even promising ideas are implemented in practice. Therefore, we investigate the implications of policy developments based on real-life experiences of informal caregivers. A directed approach to qualitative context analysis was applied. We conclude that these democratic values should be inextricably related and (re)balanced to substantively realise the citizenship and rights of disabled people and their informal caregivers in practice.